The Effects of financialisation on development in South Africa - Chipangila, Chitalu Joshua (Graduate School of Business (GSB), 2020)
Interest in the concept of financialisation has gained traction in both developed and emerging markets. With roots embedded in the economic theory of neo-liberalism, the concept of financialisation can be broadly defined as the growing importance of financial instruments and the financial sector. A large body of empirical work in developed markets has generally indicated a negative association between financialisation and various socio-economic indicators. However, the limited empirical evidence in emerging markets has proved inconsistent. This study examines the presence of financialisation in South Africa since the start of the democratic era covering 1994 to 2017, and explores the relationship between financialisation and several key socio-economic factors in the country including economic growth, investment, inequality, unemployment and innovation. Financialisation is measured using two generally accepted proxies - the contribution of the financial sector to total value added in the economy and the percentage of people employed in the financial sector. In addition, two other measures are used based on the work of Krippner (2005) with the first the ratio of portfolio income generated by non-financial firms relative to revenue yielded by productive activities and the second the ratio of the financial sector's revenue contribution to the economy in relation to the non-financial sector. The Autoregressive Distributive-Lag (ARDL) model is used to examine the long-run and short-run associations between financialisation and the key development indicators. The study finds evidence in support of the occurrence of financialisation in South Africa post 1994. The results of the statistical analysis reveal that for the generally accepted proxies for financialisation, financialisation has a positive effect on unemployment reduction and economic growth, no effect on inequality reduction and investment, while the evidence with regards to innovation is mixed. The additional results from the Krippner financialisation ratios indicate that financialisation has a positive effect on inequality reduction and economic growth, a negative effect on innovation and investment, while no effect on unemployment reduction. The findings of this study contradict theoretical expectations, as they point to some positive effects of financialisation on the South African economy although there are also some negative effects. In light of this, policy recommendations are provided so as to enhance these positive effects while also safeguarding against further negative effects.